Development of the University of Wisconsin running injury and recovery index - Nelson, E. O.; Ryan, M.; AufderHeide, E.; Heiderscheit, B. (Journal of Orthopaedic & Sports Physical Therapy, 2019)
Runners experience a high proportion of overuse injuries, with extended recovery periods involving a gradual, progressive return to preinjury status. A running-specific patient-reported outcome (PRO) measure does not exist, and a questionnaire assessing critical elements of runners' recovery processes may have excellent psychometric properties. Objectives